The Relationship of Physical Freshness to Student’s Learning Outcomes in 16 OKU Public Elementary Schools - Yulita, Yulita; Manullang, Jujur Gunawan; Hermansah, Bambang (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the level of physical freshness of students and student learning outcomes, as well as to determine the relationship between the level of physical freshness and the learning outcomes of students of State Elementary School 16 OKU. The population in this study was grade V students of State Elementary School 16 OKU with a sample of 30 students. The sampling technique used is random sampling. The data collection method uses a survey method with the Indonesian Physical Freshness Test (TKJI) method and documentation. Data from test results are processed using computerized SPSS system version 23. The results showed: 1) the level of physical freshness of grade V students of State Elementary School 16 OKU in the medium category. 2) Learning outcomes of grade V students of State Elementary School 16 OKU in the good category. 3) there is a significant positive relationship between the level of physical freshness and the learning outcomes of grade V students Public Elementary School 16 OKU. Students are expected to always maintain and improve their physical freshness as the main provision for the learning process.